2016
DOI: 10.1073/pnas.1609470113
|View full text |Cite
|
Sign up to set email alerts
|

Fractional charge and inter-Landau–level states at points of singular curvature

Abstract: The quest for universal properties of topological phases is fundamentally important because these signatures are robust to variations in system-specific details. Aspects of the response of quantum Hall states to smooth spatial curvature are well-studied, but challenging to observe experimentally. Here we go beyond this prevailing paradigm and obtain general results for the response of quantum Hall states to points of singular curvature in real space; such points may be readily experimentally actualized. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The TLD-bound modes carry nonzero orbital angular momentum (OAM), locked to their propagation direction. For each k z , the sign of the OAM depends on the Chern number of the 2D projected band structure, and matches the chirality of the robust localised state that appears in a Chern insulator on a 2D surface with singular curvature 42 45 —a prediction that has never previously been verified in an experiment 8 , 46 , 47 . To our knowledge, this is also the first demonstration of a 3D topology-induced mode carrying nonzero OAM.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The TLD-bound modes carry nonzero orbital angular momentum (OAM), locked to their propagation direction. For each k z , the sign of the OAM depends on the Chern number of the 2D projected band structure, and matches the chirality of the robust localised state that appears in a Chern insulator on a 2D surface with singular curvature 42 45 —a prediction that has never previously been verified in an experiment 8 , 46 , 47 . To our knowledge, this is also the first demonstration of a 3D topology-induced mode carrying nonzero OAM.…”
Section: Introductionsupporting
confidence: 55%
“…For each momentum space slice ( k z ), the system maps onto a 2D Chern insulator trapped on a surface with singular curvature. Theoretical studies have previously shown that such a system hosts a robust localised defect mode tied to the Chern number of the 2D bulk bandstructure 8 , 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of a Chern number, and/or non-trivial rotation invariants this flux traps charge. A similar effect is known in the quantum Hall effect literature where the U (1) electromagnetic field can couple, in the presence of continuous rotation symmetry, to the geometric spin-connection field with the Wen-Zee term [52][53][54][55]…”
Section: Fractional Disclination Charge For Tcis With Chern Numbermentioning
confidence: 81%
“…Another appealing feature of our platform is the possibility of engineering periodic boundary conditions, as explicitly shown in the 1D Haldane-Shastry model, or other global lattice topology by introducing long-range interactions between spins located at the boundaries of a finite system. Using 2D PCWs, for example, it is possible to create novel spin-lattice geometries such as Möbius strip, torus, or lattice models with singular curvatures such as conic geometries [79] that may lead to localized topological states with potential applications in quantum computations.…”
Section: Discussionmentioning
confidence: 99%